2020
DOI: 10.1155/2020/8865841
|View full text |Cite
|
Sign up to set email alerts
|

Bionic Silk Fibroin Film Induces Morphological Changes and Differentiation of Tendon Stem/Progenitor Cells

Abstract: Purpose. Tendon injuries are common musculoskeletal system disorders, but the ability for tendon regeneration is limited. Silk fibroin (SF) film may be suitable for tendon regeneration due to its excellent biocompatibility and physical properties. This study is aimed at evaluating the application value of bionic SF film in tendon regeneration. Methods. Tendon stem/progenitor cells (TSPCs) were isolated from rat Achilles tendon and characterized based on their surface marker expression and multilineage differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…TSPCs were isolated from tendon tissues of three 8-week old male Sprague-Dawley (SD) rats as three independent biological samples and identified for their cell surface marker expression and multi-directional differentiation potential, as our previous study [ 33 , 53 ]. All procedures and experiments were approved by the Ethics Committee of Army Medical University (Chongqing, China) and performed, according to the guidelines of the National Institutes of Health for the Care and Use of Laboratory Animals [ 53 , 54 ]. The TSPCs were cultured in F12 complete media, which were changed every three days and the cells were passaged every xxx days.…”
Section: Methodsmentioning
confidence: 99%
“…TSPCs were isolated from tendon tissues of three 8-week old male Sprague-Dawley (SD) rats as three independent biological samples and identified for their cell surface marker expression and multi-directional differentiation potential, as our previous study [ 33 , 53 ]. All procedures and experiments were approved by the Ethics Committee of Army Medical University (Chongqing, China) and performed, according to the guidelines of the National Institutes of Health for the Care and Use of Laboratory Animals [ 53 , 54 ]. The TSPCs were cultured in F12 complete media, which were changed every three days and the cells were passaged every xxx days.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation and Characterization of SF Films. SF films were prepared as previously described [21,22]. Briefly, the SF solution was dried to form smooth or micropattern films on polydimethylsiloxane (PDMS) plate, and their stability was improved by water-annealing treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, bionics has emerged as a new direction in the design and preparation of biomaterials for tissue repair [14,[18][19][20]. In our previous studies, we demonstrated that SF films mimicking the physical surface micropattern of fiber morphology of native tendon collagen can promote the tenogenic differentiation of tendon stem/progenitor cells (TSPCs) [21,22]. However, the repairing effect of micropattern SF films in tendon injury and their effect on regulating the intrinsic TSPC signaling pathways remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering is a promising therapeutic modality for the reconstruction of ligaments and tendons. Silk fibroin scaffold has found as an appropriate biomaterial being utilized for this purpose [134,135]. Tellado et al, was constructed a dual characteristic silk fibroin scaffold that contains two diverse pore arrangements.…”
Section: Ligament Tissue Engineeringmentioning
confidence: 99%
“…Lu et al investigated the mechanical attributes of silk fibroin in tendon reconstruction. They concluded that the artificial micro-fabrication on the surface of silk fibroin film contributes remarkable biological supervision in the growth of tendon stem/progenitor cells (TSPCs) that quality makes silk fibroin film an effective ingredient for the reconstruction of the tendon tissue [135].…”
Section: Ligament Tissue Engineeringmentioning
confidence: 99%